PENYULUHAN ASI EKSKLUSIF, PIJAT OKSITOSIN DAN PENGENALAN MP-ASI SEBAGAI PERSIAPAN BAYI LULUS 6 BULAN - Siti Yulaikah (Universitas Mataram, 2022)
Full breastfeeding for 6 months is highly recommended because breast milk is very important for optimal growth and development of babies both physically and mentally and also for baby’s intelligence. To suffice babies needs of breast milk, so it’s needed an oxytocin massage. Oxytocin massage enabled for increase milk production. After the baby reaches the age of 6 months, the need for nutrients increases, therefore the baby is still given breast milk and supplemented with complementary foods (MP-ASI). The goal of the activity is to increase knowledge of breastfeeding mothers about exclusive breastfeeding, how to increase the production of breast milk with oxytocin massage, recognize the signs that babies are ready to receive supplemented with complementary foods (MP-ASI), and how to make complementary foods (MP-ASI) as a preparation for babies entering the age of 6 months and over. This Community Activity uses the health education method with using lecture techniques, question and answer, demonstration or practice and evaluation. The target audience is breastfeeding mothers who have babies aged 1-6 months as many as 20 participants. It will be held at the Kemudo Prambanan village hall, Klaten, November 2, 2021, at 08.00 – 12.00 WIB. The health education that given to breastfeeding mothers has an impact on increasing knowledge of breastfeeding mothers. This can be seen in the results of the pre-test and post-test scores, it was found that the majority of breastfeeding mothers' knowledge had increased in the good category. Knowledge is a very important factor because good knowledge can raise awareness for positive behavior. Providing information to increase knowledge so as to raise awareness, one of which is by providing information in the form of health education. A research explained that a person's level of knowledge will increase after that person gets an explanation from competent parties in it. The health education that has been carried out in this activity has an impact on increasing the knowledge of breastfeeding mothers in the good category.